Alone [videorecording (Blu-Ray)] - Willcox, Jules, 1980-; Menchaca, Marc, 1975-; Heald, Anthony (Magnolia Home Entertainment, 2020)
Set in the Pacific Northwest wilderness, the film follows recently widowed Jessica who, fleeing the city in a desperate attempt to cope, is kidnapped and locked away in a mysterious man's cabin. Her escape from the clutches of this murderous captor land her in the heart of the untamed wilderness, with only her wits to rely on for survival as her pursuer closes in.